Effect Of Fibre Tapering On The Laser Diode-Fibre Coupling - Sambanthan, Kumaran (2006)
This thesis will examine the use of 1550 nm laser diode as the light source for the study on the tapered fibres effectiveness to improve coupling efficiency. We studied a method to improve the coupling efficiency of light from a laser diode to an asymmetric tapered hemispherical lensed fibre. The method involves using HF acid to improve the mode mismatch between the laser diode and lensed fibre.